Adapting agile methods to support creativity in interdisciplinary projects - André Jeworutzki (2013)
This thesis is about the question whether agile methodologies are suited to support creativity in interdisciplinary projects and what adjustments would be necessary for this purpose. These studies are based on observations made in preliminary studies about interaction design. For this, projects are considered as an integrated system where actors, methods and surrounding conditions interact with each other. With regard to creativity, conclusions are drawn from these interactions in order to Vnd appropriate measures and adaptations.